Listening to the consumer voice: developing multilingual cancer information resources for people affected by liver cancer. (29th February 2016) - Robotin, Monica C.; Porwal, Mamta; Hopwood, Max; Nguyen, Debbie; Sze, Minglo; Treloar, Carla; George, Jacob
Abstract: Background: In Australia, liver cancer incidence is rising, particularly among people born in hepatitis B‐endemic countries. We sought to build an understanding of the information needs of people affected by liver cancer, to inform the design of in‐language consumer information resources. Methods: We searched the World Wide Web for available in‐language consumer information and conducted a literature search on consumers' information needs and their preferred means of accessing it. Qualitative data collection involved bilingual researchers conducting focus group discussions (26 participants) and in‐depth interviews (22 participants) with people affected by liver cancer in English, Vietnamese, Cantonese and Mandarin. Sessions were audio‐recorded, transcribed, translated and thematically analysed. The key themes and salient findings informed the development of in‐language multimedia information resources. Results: Many consumer resources did not cater for people with low literacy levels. The participants wanted more information on cancer diagnostic and treatment options, nutrition and Chinese Medicine and experienced communication challenges speaking to health professionals. While Vietnamese speakers relied entirely on information provided by their doctors, other participants actively searched for additional treatment information and commonly used the Internet to source it. We developed multilingual, multimedia consumer information resources addressing identified consumer information needs through an iterative process, in collaboration with our multilingual consumer panel. These resources are available in four languages, as separate modules accessible online and in DVD format. Conclusion: This process enabled the development of user‐friendly patient resources, which complement health‐care provider information and supports informed patient decision making.